Revenue sharing contract for a VMI with one for one period policy. Issue 1 (1st January 2018) - Haji, Alireza; Afzalabadi, Maryam; Haji, Rasoul
Abstract: In this article, we design a revenue-sharing contract to coordinate inventory control decisions in a serial supply chain consisting of one supplier, one vendor, and one retailer. We assume that the retailer faces Poisson demand and his unsatisfied demands will be lost. The retailer applies one-for-one period policy in which he constantly places an order for one unit of product to the vendor in a predetermined time interval which results in a deterministic demand for the vendor. Vendor orders the required quantity from supplier which will be immediately received at the vendor's warehouse. Solution procedures are developed to find the equilibrium in the vendor managed inventory program with a revenue-sharing contract. Furthermore, we obtain the optimal order cycle for the retailer and the vendor which minimizes the supply chain's total cost.